Phonological fossilization of Arabic pronunciation among Malays: a review article - Muhammad Ridha Ali Huddin (Tanjong Malim, 2022)
Phonological fossilization of Arabic pronunciation among Malays: a review article by Muhammad Ridha Ali Huddin